1) 2x+y=11 2) 5x-2y+6 3) 3x-2y=30
2x-y=9, 7x+2y=18, x-4y=25, умножаем на (-3)
4x=20, 12x=24, 3x-2y=30
x=5 x=2 -3x+12y= -75,
10y= -45
2y= -9
y= -2/9
Объяснение:
-3u+5v=1.5 домножим обе части уравнения на -3,получаем
9u-15v=4.5
система принимает вид. можем применить метод сложения (аналогично А)
11u+15v=1.9
9u-15v=4.5
2х-3у = -8
х=7-4у20v=6.4
v=0.32
-3x + 10 = -3x - 6
10 = -6
б) -3x + x - 5 = -2x - 8
-2x -5 = -2x -8
-5 = -8
в) x = 1 - 6
x = -5
г)-2 (x - 4) = 5 (1 - 3x)
-2x + 8 = 5 - 15x
-2x + 15x = 5 - 8
13 = -3
д)6 (1 - x) + 10 (2x - 4) = 3 (x + 3)
6 - 6 x + 20x - 40 = 3x + 9
-34 + 14x = 3x + 9
14x - 3x = 9 + 34
11x = 43
x = 43/11
е)9x^2 - 4 - (9x^2 - 2x + 16) = 28
9x^2 - 4 - 9x^2 + 24x - 16 = 28
-20 + 24x = 28
24x = 28 +200
24x = 48
x = 2